Integration of wastewater electro-electrodialysis and CO2 capture for sustainable LIB recycling: Process design and economic analyses. (10th March 2023) - Kim, Jeongdong; Moon, Il; Kim, Junghwan
Abstract: Hydrometallurgy-based recycling processes for spent lithium-ion batteries (LIB) can be conducted under mild operating conditions while achieving a high metal recovery rate. However, due to the excessive use of chemicals during operation, issues associated with operating costs and pollution of disposed wastewater hinder large-scale application. The disposed wastewater contains highly concentrated ions that can be reutilized via electro-electrodialysis (EED). In addition, regenerated base can be utilized as a CO2 absorbent, which produces soda ash that can be directly utilized for metal precipitation in the recycling process. Thus, this paper proposes a novel integrated system of wastewater EED and CO2 capture for sustainable LIB recycling. This system includes selective metal recovery of cathode material, wastewater EED, and CO2 capture and utilization. Based on the simulation results, system performance was evaluated considering the regenerated chemical concentration and its impact on the metal recovery rate. The complete regeneration of 2.04 M sulfuric acid and 1.09 M caustic soda solutions could be accomplished from the waste liquid. In recycling capacity of 50, 000 ton/year, 0.33 kg of CO2 could be captured per 1 kg of LCO cathode material, and 99% selective metal extraction could be accomplished during battery recycling using the regenerated chemicals. To clarify economic performance, the levelized cost of recycling was analyzed in different market scenarios for chemicals. The proposed system can accomplish full regeneration of wastewater via EED with a 21.90% lower levelized cost of recycling compared with the conventional system. The results of simulation and economic analysis demonstrate the potential performance of the proposed system in terms of sustainability and economic feasibility in current LIB recycling industry. Graphical abstract: Image 1 Highlights: Electro-electrodialysis and CO2 capture and utilization integrated to recycle LIB. Full regeneration of 2.04 M sulfuric acid and 1.09 M caustic soda was accomplished. 0.33 kg/kgLCO of CO2 was captured and 99% battery recycling was accomplished. A solution for waste-free recycling of large-scale cathode material is proposed.